Biosorption of Copper from Aqueous Solutions Using Tridax procumbens - Thirunavukkarasu1; S. Ramesh2ï€ª, T. Karthika1, A. (Recent Research in Science and Technology, 2010)
Bioremediation of heavy metal pollution remains a major challenge in environmental biotechnology. Many plants have been shown to bind heavy metals with varying degrees of specificity and affinity. This paper highlights the potential of Tridax procumbens for biosorbing copper metal ion in aqueous solutions. Experiments were carried out as a function of pH, biosorbent concentration, copper concentration, contact time. A removal of 91% was achieved under optimized conditions. At pH 5 the maximum adsorption capacity of Cu was observed. The mechanism of metal sorption by Tridax procumbens gave good fits for Freundlich and Langmuir models.